DIGITAL BANKS: COMPETITORS OR PARTNERS TO THE TRADITIONAL BANKING SYSTEM? (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the impact of digital banks on the traditional banking system, focusing on whether they act as competitors or partners. It highlights the main features and advantages of digital banking, including speed, convenience, and cost efficiency, as well as the challenges faced by traditional banks in adapting to technological change. The study also explores the growing competition driven by customer preferences, particularly among younger users, and emphasizes the role of collaboration between fintech companies and traditional financial institutions. The findings suggest that rather than completely replacing traditional banks, digital banks contribute to the modernization and increased efficiency of the banking sector through integration and innovation.